Financial Inclusion and Economic Growth in Nigeria - Grace U. Nwansi; Samuel Dibiah (Research Parks Publishers, 2023)
This study examined the relationship between financial inclusion and economic growth in Nigeria. The study employed the Ordinary Least Square multiple regression to analyze the data obtained from secondary sources for the period 1991-2021. The findings revealed that combined effect of ratio of broad money to GDP, credit to private sector to GDP, aggregate loan-to-deposit ratio and liquidity ratio of commercial banks influenced economic growth in Nigeria. Based on the findings from the study, the researcher therefore conclude that the provision of banking services to the unbanked and active poor will contribute positively to the growth of Nigeria economy and recommends that banks should be encouraged to grant loans to private businesses and small scale enterprises so as to further promote economic growth.